PENINGKATAN SIKAP DEMOKRATIS SISWA MELALUI METODE BERMAIN PERAN DALAM PEMBELAJARAN PKn - SUNARYATI, TITIN (JURNAL PENDIDIKAN DASAR, 2012)
The research is to find the increasing of democratic affective in PKn learning trhough Role Play Methode. This reasearch was implemented at MI Al Muhajirien Jakapermai Bekasi with 40 students as subject of research.This is an action research by using Kemmis and Taggart model in two cycles. Each cycle consists of planning, acting, observing and reflecting.The qualitative result of this action research showed that student democratic affective can increase the student personality with good character and the implementation of role play method made students happy and active .In other side the quantitative result showed the increasing of percentage anquete from 55% to 68% in cycle I and become 92,5 % in cycle II. In both cycles, students achieved the minimum mastery criteria. The observation result of activity of role play methode of both teacher and students in cycle II achieved 100% of mastery learning.Finally from both qualitative data and quantitative data indicate that PKn learning activities by using role play method can increase the democratic affective of students